PENGEMBANGAN MEDIA EDUKASI PEMBELAJARAN MUATAN LOKAL DAERAH ALIRAN SUNGAI DAN DANAU MODEL ADDIE PADA SISWA KELAS V - Dinda Lamuda; Razak H Umar; Dewi Darmiyani Napu (Al-mujahidah, 2026)
This study aims to develop educational E-Comic media in local content learning about river basins and to determine the feasibility of the media based on the assessment of material experts, language experts, design experts, teacher responses, and responses from fifth-grade students of SDN 11 Limbto. The problem found in local content learning for fifth-grade elementary school is the unavailability of educational E-Comic-based learning media that combines visual and story elements in delivering river basin material. This study uses the R&D method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of the study show that the feasibility aspect of the developed educational E-Comic media obtained a validation percentage of material experts of 90%, validation of language experts of 97%, and validation of design experts of 100%. In addition, the results of the teacher response questionnaire obtained a percentage of 82% and the results of the student response questionnaire obtained a percentage of 89%. Therefore, the educational E-Comic media in local content learning about river basins that was developed is in the category of very suitable for use in learning activities in elementary schools.